FACTORY OF PROCESSES – NEW FORMAT OF ORGANIZATION OF EDUCATIONAL PROCESS IN HIGHER EDUCATIONAL INSTITUTION - Albert Akhmetovich Kurmangulov; Julia Sergeevna Reshetnikova; Julia Sergeevna Reshetnikova; Roman Nazimovich Bagirov; Roman Nazimovich Bagirov; Olga Igorevna Frolova; Olga Igorevna Frolova; Natalya Semenovna Brynza; Natalya Semenovna Brynza (Высшее образование в России)
The article deals with the technology of organization of the educational process in a higher educational institution with the application of the interactive method of training – factorу of processes. The comparative characteristics of the methodology of factorу of processes are given, general content-technological determinants with the format of the business game are shown, as well as their distinctive features. A sufficiently large variational scenario potential of factorу of processes with the obligatory inclusion of a number of stages is shown. The experience of implementing the factorу of processes in the educational process of the Tyumen State Medical University in the framework of the program "Lean production in health care" is demonstrated. The article shows the high potential for incorporating the format of the factorу of processes into the educational process with obtaining the necessary competencies and aiming at using the acquired skills in further practical activities